2019
DOI: 10.36543/kauiibfd.2019.035
|View full text |Cite
|
Sign up to set email alerts
|

Dönüştürücü Li̇derli̇k Ve Örgütsel Yeni̇li̇kçi̇li̇k Arasindaki̇ İli̇şki̇: Bi̇r Kamu Kurumu Örneği̇

Abstract: The main objective of this study is to examine the relationship between transformational leadership behavior and organizational innovativeness perception of officers currently working at the Governorship of Ardahan and its associated departments. Although there exists a fairly large literatüre for private sector firms, the number of studies concerning organizational innovation facilities for public institutions is relatively limited. For this purpose; firstly, the concepts of transformational leadership and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The existence of organizations in a dynamic and intense environment causes organizations to have difficulties in their activities. For this reason, many organizations need to adopt organizational innovation, which is seen as the source of their competitive leadership [1].…”
Section: Literaturementioning
confidence: 99%
“…The existence of organizations in a dynamic and intense environment causes organizations to have difficulties in their activities. For this reason, many organizations need to adopt organizational innovation, which is seen as the source of their competitive leadership [1].…”
Section: Literaturementioning
confidence: 99%
“…This change should be encouraged by the leader, with the indication that it will benefit group members as well [13]. Several leadership approaches can be applied to school development to achieve a school's vision [14][15][16][17][18][19][20][21][22][23][24][25]. Several scholars have drawn attention to the importance of ethical leadership [26,27].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Bu araştırma kapsamında ele alınan dönüştürücü liderlik değişkeni ile ilgili literatürde çeşitli araştırmalar yer almaktadır. Bu araştırmalarda, dönüştürücü liderliğin örgütsel bağlılığa etkisi (Demirtaş ve Şama, 2016;Erdoğan Morçin ve Bilgin, 2014), dönüştürücü liderliğin öğretmenlerin iş doyumu ve yenilikçi davranışlarıyla ilişkisi (Çobanoğlu, 2021), dönüştürücü liderlik davranışlarının iş tatmini üzerindeki etkisi (Mert, Dördüncü ve İncaz, 2019), dönüştürücü liderlik ile yenilikçilik arasındaki ilişki (Aarons ve Sommerfeld, 2012;Çalışkan, 2017;Jaiswal ve Dhar, 2015;Sarros, Cooper ve Santora, 2008), dönüştürücü liderlik ile genel öz yeterlik arasındaki ilişki (Sığrı, Tabak ve Güngör, 2010), dönüştürücü liderliğin cinsiyet rolüne bağlı olarak ne kadar farklılaştığı (Arslan, 2014), dönüştürücü liderliğin bireysel ve örgütsel düzeydeki yaratıcılık üzerine etkisi (Gümüşoğlu ve İlsev, 2009), dönüştürücü liderlik ile öğrenme yönelimi arasındaki ilişki (Coad ve Berry, 1998) üzerine çalışıldığı görülmüştür. Bunların yanı sıra Zengin (2019) yaptığı çalışmada dönüştürücü liderliğin rekabet üstünlüğü performansı üzerindeki dolaylı etkisini incelemiştir.…”
Section: Introductionunclassified
“…It was observed that these studies were about the effects of transformational leadership on organizational commitment (Demirtaş & Şama, 2016;Erdoğan Morçin & Bilgin, 2014), the relationship of transformative leadership with teachers' job satisfaction and innovative behaviors (Çobanoğlu, 2021), the effect of transformative leadership behaviors on job satisfaction (Mert, Dört, & İncaz). , 2019), the relationship between transformative leadership and innovation (Aarons & Sommerfeld, 2012;Çalışkan, 2017;Jaiswal & Dhar, 2015;Sarros, Cooper & Santora, 2008), the relationship between transformative leadership and self-efficacy (Sığrı, Tabak & Güngör , 2010), the differences in transformative leadership by gender (Arslan, 2014), the effect of transformative leadership on creativity at individual and organizational level (Gümüşoğlu & İlsev, 2009), the relationship between transformative leadership and learning orientation (Coad & Berry, 1998). Additionally, Zengin (2019) investigated the indirect effect of transformational leadership on competitive advantage performance.…”
Section: Introductionmentioning
confidence: 99%